Pengaruh Pembiasaan Membaca Al Qur’an Terhadap Kecerdasan Emosional Dosen dan Tendik Fakultas Teknik dan Ilmu Komputer UMPP - Sulaiman, Muh Andi; Rosanti, Cholisa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Regular reading of the Qur'an is believed to have a positive impact on a person's life, including its potential influence on emotional intelligence. Such as increased patience and calm, increased empathy and caring, increased ability to manage emotions, improved social relationships. The influence of the habit of reading the Koran on emotional intelligence is very interesting to research. Therefore, this research will be carried out on UMPP lecturers and staff. This research will explain the influence of the habit of reading the Koran on the emotional intelligence of lecturers and staff at the Faculty of Engineering and Computer Science, UMPP. This research method uses descriptive analysis, namely a type of data analysis used to show, display, describe and summarize a set of data. The aim is to identify trends and patterns in the data and to obtain in-depth data, data that contains meaning and can significantly influence the substance of the research. The data used includes the results of interviews regarding the effectiveness of the habit of reading the Koran on the emotional intelligence of lecturers and Tendik In this research the researcher used a descriptive research strategy. The research results show that reading the Koran regularly can have a positive impact on a person's emotional intelligence. The content of the Qur'an often teaches values such as patience, gratitude, forbearance, self-control and empathy. Meditating on verses from the Koran can help a person increase self-awareness, regulate emotions, and develop empathy towards others. Reading the Koran is not just reading, but also a process of contemplating its meaning and relating it to everyday life.